Characterization of the genetic composition and establishment of a core collection for the INERA Robusta coffee (Coffea canephora) field genebank from the Democratic Republic of Congo - Verleysen, Lauren; Bollen, Robrecht; Kambale, Jean-Léon; Ebele, Tshimi; Katshela, Benjamin Ntumba; Depecker, Jonas; Poncet, Valérie; Assumani, Dieu-Merci; Vandelook, Filip; Stoffelen, Piet; Honnay, Olivier; Ruttink, Tom (Frontiers in Sustainable Food Systems, 2023)
Cultivation of Robusta coffee is likely to gain importance because of its high disease resistance and climate envelope. Robusta coffee genetic resources conserved in field genebanks can play an important role to further improve its cupping quality and other agronomic traits, but such Coffea canephora collections are limited and still poorly characterized. In this study, we characterized the genetic composition of the historically important but until recently neglected INERA Coffee Collection in Yangambi (the Democratic Republic of Congo). We used GBS to discover genome-wide genetic diversity, created and validated a novel multiplex amplicon sequencing (HiPlex) screening assay to genetically screen 730 coffee shrubs of the Yangambi Coffee Collection, grouped clonal material and delineated 263 accessions with unique genetic fingerprints. Comparison to reference material of three genetic origins revealed that the majority of the Yangambi accessions were assigned a ‘Lula’ cultivar origin, four accessions were assigned to Congolese subgroup A and nine accessions were most closely related to local wild accessions. About one-quarter of the accessions was likely derived from hybridization between these groups, which could result from seed-based propagation of the collection, breeding efforts, or natural cross-pollination. Parental analyses discovered eight preferentially used accessions, which may correspond to historically selected founders, or direct descendants thereof, whose seed material was once widely used to establish coffee plantations. Finally, two core collections were proposed using the maximization strategy (CC-I; 100 accessions) and genetic distance method (CC-X; 10 accessions). Our study demonstrates a method for the genetic characterization of Robusta coffee collections in general and contributes to the re-evaluation and exploration of the Robusta coffee genetic resources in the Democratic Republic of the Congo in particular.